Using group work to harness students’ multilinguistic competencies for a better understanding of assignment questions - Ramchander, Manduth (Critical Studies in Teaching and Learning, 2023)
In South Africa, it is readily acknowledged that there is an absence of pedagogy to inform multilanguage usage for students for whom English is not a first language. Equally noteworthy, is that while group work has been used extensively as an active learning methodology, which has not been explored to the same extent is the manifestation of translanguaging when working in groups. This study explored how best to harness students’ multilingual competencies for a better understanding of assignment questions. The population comprised of first year Business Communication students at a university of technology. A mixed method research design revealed that when multilingual students engaged in group work, there was a tendency of gravitation towards translanguaging which resulted in students having a better understanding of assignment questions. It was concluded that group work can serve as an enabler for translanguaging, harnessing students’ multilingual competencies for a better understanding of their work.